A Critical Study of Book of Historiography: An Introduction - Mohsen Morsalpour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book, Historiography: An Introduction, written in seven chapters by Roger Spalding and Cristopher Parker has studied various issues in the field of historiography and has explored contents on the philosophy of history and the method of research in history. The authors place their emphasis on the science of history (history as a report) and consider the essential components of historical inquiry as the study of historical and intellectual schools. The authors have, therefore, studied schools such as the Whig historiography, progressive Idea, National Socialism, Gender in history, Marxism, and cultural history. These sections can be a model for studying historical and intellectual schools. In addition, writers have written about undergraduate essay writing tips that are useful for students. The present article, using an analytical approach, critically reviews the book and concludes that despite its weaknesses, defects of writer’s theories, and limited perspective, it is a useful guide for undergraduate essay writing and a good model for studying historical schools.